European Pediatric Surgeons' Association Survey on the Use of Splenic Embolization in Blunt Splenic Trauma in Children - Dariel, Anne; Soyer, Tutku; Dingemann, Jens; Pini-Prato, Alessio; Martinez, Leopoldo; Faure, Alice; Oumarou, Mamane; Hassid, Sophie; Dabadie, Alexia; De Coppi, Paolo; Gorter, Ramon; Doi, Tkashi; Antunovic, Sanja Sindjic; Kakar, Mohit; Morini, Francesco; Hall, Nigel J. (European Journal of Pediatric Surgery, 2022)
Introduction This article assesses (1) access to splenic embolization (SE), (2) indications for SE, and (3) post-embolization management in high-grade splenic trauma in children.Materials and Methods An online questionnaire was sent in 2021 to all members of European Pediatric Surgeons' Association.Results There were a total of 157 responses (50 countries, 83% academic hospitals). Among them, 68% have access to SE (SE) and 32% do not (nSE). For a hemodynamic stable patient with high-grade isolated splenic trauma without contrast extravasation (CE) on computed tomography (CT) scan, 99% SE and 95% nSE respondents use nonoperative management (NOM). In cases with CE, NOM decreases to 50% (p = 0.01) and 51% (p = 0.007) in SE and nSE centers, respectively. SE respondents report a significant reduction of NOM in stable patients with an associated spine injury requiring urgent surgery in prone position, both without and with CE (90 and 28%, respectively). For these respondents, in stable patients the association of a femur fracture only tends to decrease the NOM, both without and with CE (93 and 39%, respectively). There was no significant difference in NOM in group nSE with associated injuries with or without CE. After proximal SE with preserved spleen vascularization on ultrasound Doppler, 44% respondents prescribe antibiotics and/or immunizations.Conclusion Two-thirds of respondents have access to SE. For SE respondents, SE is used even in stable patients when CE showed on initial CT scan and its use increased with the concomitant need for spinal surgery. There is currently a variation in the use of SE and antibiotics/immunizations following SE.
Keywords: splenic trauma; embolization; children; survey